Stakeholders’ Perspectives for the Development of a Point-of-Care Diagnostics Curriculum in Rural Primary Clinics in South Africa—Nominal Group Technique - Nkosinothando Chamane; Desmond Kuupiel; Tivani Phosa Mashamba-Thompson (Diagnostics, 2020)
Poor knowledge and adherence to point-of-care (POC) HIV testing standards have been reported in rural KwaZulu-Natal (KZN), a high HIV prevalent setting. Improving compliance to HIV testing standards is critical, particularly during the gradual phasing out of lay counsellor providers and the shifting of HIV testing and counselling duties to professional nurses. The main objective of this study was to identify priority areas for development of POC diagnostics curriculum to improve competence and adherence to POC diagnostics quality standards for primary healthcare (PHC) nurses in rural South Africa. Method: PHC clinic stakeholders were invited to participate in a co-creation workshop. Participants were purposely sampled from each of the 11 KwaZulu-Natal Districts. Through the Nominal Group Technique (NGT), participants identified training related challenges concerning delivery of quality point of care diagnostics and ranked them from highest to lowest priority. An importance ranking score (scale 1–5) was calculated for each of the identified challenges. Results: Study participants included three PHC professional nurses, one TB professional nurse, one HIV lay councilor, one TB assistant and three POC diagnostics researchers, aged 23–50. Participants identified ten POC diagnostics related challenges. Amongst the highest ranked challenges were the following:absence of POC testing Curriculum for nurses, absence of training of staff on HIV testing and counselling as lay counsellor providers are gradually being phased out,. absence of Continuous Professional Development opportunities and lack of Staff involvement in POC Management programs. Conclusion: Key stakeholders perceived training of PHC nurses as the highest priority for the delivery of quality POC diagnostic testing at PHC level. We recommend continual collaboration among all POC diagnostics stakeholders in the development of an accessible curriculum to improve providers’ competence and ensure sustainable quality delivery of POC diagnostic services in rural PHC clinics.